The impact of DNA damage repair inhibitors on the therapeutic window of thoracic radiation - Martin, J (2020)
Background: Lung cancer is the leading cause of cancer death worldwide. A mainstay of treatment is radiotherapy, although its efficacy is limited by toxicity to surrounding normal tissue. New combination treatments are being proposed to increase the radiotherapy anti-tumour effect, but there has been a lack of preclinical studies looking at normal tissue effects simultaneously.